2016
DOI: 10.18553/jmcp.2016.22.11.1319
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Rivaroxaban, Dabigatran, and Apixaban for Stroke Prevention in Incident, Treatment-Naïve Nonvalvular Atrial Fibrillation

Abstract: BACKGROUND Non-vitamin K antagonist oral anticoagulants (NOACs) are widely used for prevention of stroke secondary to nonvalvular atrial fibrillation (NVAF). Increased use of NOACs is partially a result of simplified regimens compared with warfarin, which has been associated with poor adherence and persistence to therapy. Few studies have assessed adherence to NOACs, especially using contemporary data now that multiple NOACs are available. OBJECTIVE To evaluate adherence to NOACs in a cohort of newly diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
48
1
9

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 45 publications
5
48
1
9
Order By: Relevance
“…The proportion of days covered did not differ significantly for patients with and without valvular disease. This is consistent with previous reports of NOAC adherence on the basis of administrative data 25. Overall, 25%, 20%, and 17% of dabigatran, rivaroxaban, and warfarin users ceased the initial anticoagulant within 90 days.…”
Section: Resultssupporting
confidence: 91%
“…The proportion of days covered did not differ significantly for patients with and without valvular disease. This is consistent with previous reports of NOAC adherence on the basis of administrative data 25. Overall, 25%, 20%, and 17% of dabigatran, rivaroxaban, and warfarin users ceased the initial anticoagulant within 90 days.…”
Section: Resultssupporting
confidence: 91%
“…14 Our study is an update of a previous study by our group, which used data from 2013 to assess adherence to NOACs. 19 Overall, results of the previous study are similar to the current study, although a slightly larger advantage for rivaroxaban versus apixaban was observed using the updated data.…”
Section: Discussionsupporting
confidence: 83%
“…Mainly, patients with gaps in therapy of 3 days or who switched to another therapy were censored. Thus, based on the results from this study and previous studies, 14,19 the censoring criteria would have a stronger effect on the dabigatran group, that is, more dabigatran users would be censored, potentially leaving a biased dabigatran user group to compare with rivaroxaban users.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…First, in well‐designed clinical trials with carefully selected and motivated patients, premature discontinuation of DOAC therapy was reported in 21–25.3% of patients . Second, while multiple studies have evaluated adherence patterns with single DOAC agents, few have compared adherence patterns between multiple DOACs or have evaluated these patterns over a longer time frame . Third, with warfarin therapy there are established patient education and management models that are associated with better clinical outcomes compared to routine care, but these models do not yet exist for DOAC therapy.…”
mentioning
confidence: 99%